High rate of profound clonal and renal responses with daratumumab treatment in heavily pre‐treated patients with light chain (AL) amyloidosis and high bone marrow plasma cell infiltrate. Issue 8 (30th April 2020) - Milani, Paolo; Fazio, Francesca; Basset, Marco; Berno, Tamara; Larocca, Alessandra; Foli, Andrea; Riva, Marcello; Benigna, Francesca; Oliva, Stefania; Nuvolone, Mario; Rodigari, Lara; Petrucci, Maria Teresa; et al.
Abstract: Daratumumab demonstrated activity in the treatment of AL amyloidosis in two recently concluded phase II clinical trials in relapsed and refractory patients. Its role in upfront therapy is under evaluation in a phase III study. In this report we evaluated the safety and efficacy of 28‐day cycles of daratumumab (single agent or combined with bortezomib or lenalidomide) in 72 previously treated patients with multiple myeloma and AL amyloidosis. Fifty (69%) were refractory to the last line of therapy. After eight infusions of daratumumab, 59 patients (82%) achieved a hematologic response, with 12 (16%) complete responses (CRs) and 30 (42%) very good partial responses (VGPRs). After 16 infusions, the quality of response improved with 22 patients (30%) achieving CR and 21 (29%) attaining VGPR. Cardiac response was observed in 11 of 37 evaluable patients (29%) and renal response in 23 of 38 patients (60%). Daratumumab is highly effective in heavily pretreated patients with relapsed/refractory AL amyloidosis and high bone marrow plasma cell burden. Renal responses, which are usually rare in this setting, were frequently observed.